Budget impact analysis for dapagliflozin in type 2 diabetes in Egypt. (2nd August 2020) - Elsisi, Gihan Hamdy; Anwar, Mohammed Moustapha; Khattab, Mohamed; Elebrashy, Ibrahim; Wafa, Alaa; Elhadad, Hemat; Awad, Mohamad; Carapinha, João L.
Abstract: Introduction: Type 2 diabetes mellitus (T2DM) is a major health problem in Egypt with a high impact on morbidity, mortality, and healthcare resources. This study evaluated the budget impact and the long-term consequences of dapagliflozin versus other conventional medications, as monotherapy, from both the societal and health insurance perspectives in Egypt. Methods: A static budget impact model was developed to estimate the financial consequences of adopting dapagliflozin on the healthcare payer budget. We measured the direct medical costs of dapagliflozin (new scenario) as monotherapy, compared to metformin, insulin, sulphonylurea, dipeptidyl peptidase-4 (DPP-4) inhibitors, thiazolidinedione, and repaglinide (old scenarios) over a time horizon of 3 years. Myocardial infarction (MI), ischemic stroke, hospitalization for heart failure (HHF), and initiation of renal replacement therapy (RRT) rates were captured from DECLARE TIMI 58 trial. One-way sensitivity analyses were conducted. Results: The budget impact model estimated 2, 053, 908 patients eligible for treatment with dapagliflozin from a societal perspective and 1, 207, 698 patients from the health insurance (HI) perspective. The new scenario allows for an initial savings of EGP121 million in the first year, which increased to EGP243 and EGP365 million in the second and third years, respectively. The total cumulative savings from a societal perspective were estimated at EGP731 million. Dapagliflozin allows for savings of EGP71, EGP143, and EGP215 million in the first, second and third years respectively, from the HI perspective, with total cumulative savings of EGP430 million over the 3 years. Conclusion: Treating T2DM patients using dapagliflozin instead of conventional medications, maximizes patients' benefits and decreases total costs due to drug cost offsets from fewer cardiovascular and renal events. The adoption of dapagliflozin is a budget-saving treatment option, resulting in substantial population-level health gains due to reduced event rate and cost savings from the perspective of the national healthcare system.